User sketches: A quick, inexpensive, and effective way to elicit more reflective user feedback - Tohidi, Maryam; Buxton, Bill; Baecker, Ronald; Sellen, Abigail (NordiCHI 2006: Changing Roles, 14-18 October 2006, Oslo, Norway, 2006)
Our aim is to introduce techniques that allow for active involvement of users throughout the design process, starting with the very early stages of ideation and exploration. The approach discussed in this study augments conventional usability testing with a user sketching component. We found that enabling users to sketch their ideas facilitated reflection, and provided a rich medium for discovery and communication of design ideas. We believe that this technique has the potential to complement usability testing in general, in order to generate “reflective” as opposed to purely “reactive” user feedback.